A promising screw-extrusion steam explosion pretreatment process: effects on the morphological and structural features of Eucalyptus woodchips. Issue 111 (17th November 2016) - Liang, Yong; Lei, Bo; Zhong, Hui-Ting; Feng, Yan-Hong; Qu, Jin-Ping
Abstract : SESE pretreatment is a continuous high-efficiency process that dramatically decreases fiber size and breaks structural recalcitrance. Abstract : The effects of continuous screw-extrusion steam explosion (SESE) pretreatment on the morphology of Eucalyptus woodchip fibers and the structures of Eucalyptus lignins were investigated. The morphologies of untreated and SESE pretreated fibers were investigated by scanning electron and optical microscopies. The resulting enzymatic mild acidolysis lignins were evaluated by nuclear magnetic resonance spectroscopy, pyrolysis-gas chromatography/mass spectrometry, thermogravimetric analysis, and gel permeation chromatography. The surface of the SESE pretreated fiber was strongly disrupted, leading to a significant decrease in fiber size. The total lignin content of the Eucalyptus fibers decreased from 31.1 to 15.1% after four SESE pretreatment cycles. Lignin molecules were subjected to competitive depolymerization and repolymerization during the SESE pretreatment. This yielded lignin macromolecules with a complex heterogeneous structure and high molecular weight. The thermal stability and char conversion rate characteristics of the lignin increased with the increasing number of SESE pretreatment cycles. SESE pretreatment is a continuous high-efficiency process. These results demonstrate that SESE pretreatment can achieve similar effects to traditional steam explosion techniques, for breaking the structural recalcitrance of lignocelluloses.